Total anomalous systemic with partial anomalous pulmonary venous connections. (December 2013) - Vallath, Gopakumar; Gajjar, Trushar; Desai, Neelam
A 9-year-old girl with cyanosis, dyspnea, and grade II clubbing was diagnosed by contrast transthoracic echocardiography and angiocardiography to have an anomalous connection of the venae cavae to the physiologic left atrium with partial anomalous pulmonary venous connection. Successful surgical correction was achieved, and the patient's recovery was uneventful.